The Content and Implementation Pathways of Adversity Quotient (AQ) Enlightenment Education in Family Education - Dan, Tang (Journal of Research in Vocational Education, 2025)
As an important indicator of Adversity Quotient (AQ), the individual's ability to cope with adversity has a profound impact on children's lifelong development. Under the background of increasing social competition and chaos of we media, its early cultivation plays a key role in children's development of socialization. For 3-12 years old children group in this paper from the microscopic field of family education, system discusses the core of the enlightenment education system, put forward situation simulation, cognitive reconstruction, practice strengthening multiple implementation path, and combining with the characteristics of family education parents role positioning and implementation strategy, to promote children's ability to resist frustration, help children comprehensive sustainable development.